2018
DOI: 10.3847/1538-4357/aaa765
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Multiplicity Meets Stellar Evolution and Metallicity: The APOGEE View

Abstract: We use the multi-epoch radial velocities acquired by the APOGEE survey to perform a large scale statistical study of stellar multiplicity for field stars in the Milky Way, spanning the evolutionary phases between the main sequence and the red clump. We show that the distribution of maximum radial velocity shifts (∆RV max ) for APOGEE targets is a strong function of log g, with main sequence stars showing ∆RV max as high as ∼300 km s −1 , and steadily dropping down to ∼30 km s −1 for log g∼0, as stars climb up … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
161
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(181 citation statements)
references
References 87 publications
19
161
1
Order By: Relevance
“…This expected behaviour is indicative of longer periods for SB1s with a giant primary component. This trend is also reported in Badenes et al (2018), who thoroughly investigated the maximum RV range as a function of surface gravity and mass. They found a similar difference between dwarfs and giants.…”
Section: Orbital Propertiessupporting
confidence: 73%
See 2 more Smart Citations
“…This expected behaviour is indicative of longer periods for SB1s with a giant primary component. This trend is also reported in Badenes et al (2018), who thoroughly investigated the maximum RV range as a function of surface gravity and mass. They found a similar difference between dwarfs and giants.…”
Section: Orbital Propertiessupporting
confidence: 73%
“…comm.). 10 http://cdsxmatch.u-strasbg.fr/#tab=xmatch& 11 RAVE internal data release -292 stars in common with APOGEE (Badenes et al 2018). Since APOGEE (DR14) is a northern-hemisphere survey covering declinations above ∼ −32 • , the overlap is necessarily small (the GES maximum declination is ∼ 12 • ).…”
Section: Comparison With Other Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the close-binary fraction (periods < 10 4 days; separation < 10 AU) increases with decreasing stellar metallicity (Grether & Lineweaver 2007;Yuan et al 2015;Badenes et al 2018;Moe et al 2019), consistent with formation of cose binaries due to disk fragmentation (Tanaka & Omukai 2014). While our eclipsing binary sample has periods much shorter than their close binaries, we investigate if our results can be explained by the metallicity dependence.…”
Section: Metallicitymentioning
confidence: 75%
“…Recent surveys (Badenes et al 2018;Moe et al 2019) report an increase of the overall binary fraction of solar-type stars when metallicity decreases. The binary fraction at [Fe/H]=-1.0 is 40 ± 6% and reaches 53 ± 12% at [Fe/H]=-3.0 according to Moe et al (2019).…”
Section: Effect Of the Binary Mass Ratio Distributionmentioning
confidence: 99%